Factors influencing consumers' adoption of cashless transaction : a study from Malaysia perspective - Sousi, Rami B N (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2021)
The growth of technology and the internet has set up a business chance for government and non-profit business. The development of cashless payment is speedily increasing over time and becoming an interesting topic and area for researchers. Many businesses consider that cashless payment is as extremely influential which is the concerns for business and financial institutions such as exposes the personal information to a possible data breach. The main objective for this study aimed to analyze the factors influencing consumers’ adoption of cashless transaction from Malaysia perspective. The quantitative research method was employed to understand the theory used that is related to the study. The study measured five independent variables which are attitude, perceived usefulness, perceived ease of use, perceived behavioral control and privacy and security. These five factors were adopted from the theory of acceptance, use of technology and the theory of planned behavior. In this study, questionnaires were established on online through Google Forums and distributed on social media platforms within the of territory Malaysia, especially in Klang Valley region and Sabah and Sarawak. A total of 391 respondents were received where the researcher stopped the data collection process because the required data was found to be 385 respondents as calculated in chapter 3.2.1. The data was analyzed using the Statistical Package for the Social Sciences (SPSS) software. In this study, description of the respondents was analyzed and explained, and reliability test was conducted to determine the stability and connectivity of the variables. The test of exploratory factor analysis and multiple regression analysis were also conducted. According to the reliability test, the Cronbach’s alpha shows that all the variables were proven to be reliable. Correlation and multiple regression results revealed significant relationship between the independent variables and dependent variable. Besides that, all five hypotheses were supported with the dependent variable which are attitude, perceived usefulness, perceived ease of use, perceived behavioral control and privacy and security. To conclude, this study has provided a detailed and thorough understanding of cashless transaction from Malaysia perspective. It has also offered recommendations and valuable information for future researchers, and also provide valuable information for government sectors, private business sectors, as it has provided a detailed and thorough understanding of cashless transaction from Malaysia perspective.